HUKUM MEREK DAN USAHA KECIL MENENGAH (UKM): UPAYA MEWUJUDKAN DAYA KOMPETITIF - Budi Agus Riswandi (Journal of Management and Business, 2004)
In Indonesia, small medium businesses will have to be competitive to face the business environment today. At this point, small medium business will have to develop a competitive and smart strategy. One of the strategies that can be developed is building a brand name. This strategy will need law enforcement support from the authority. Good law enforcement can protect small businesses from piracy. In the long run, small medium businesses can build a strong brand so they can have good competition. The author will start by explaining about small medium business and the brand building strategy, then continued by exploring Indonesian brand name law. The author also give some example and the conclusion.